Stepwise approach for formulating Kenya's country-level target goals for elimination of taenia solium taeniosis/cysticercosis (one of the top ranked foodborne parasitic hazards globally) - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Kenya's National Action Plan includes this stepwise approach, which is being implemented as an approach at national level and down to local government. As implementation is still in process, we keep this as stage 1. Government documents are not available, but link to descriptive work has been provided.